Effect of Binder, Concentration, and Particle Size on Spent Coffee Grounds Briquette - Akhlis Rahman Sari Nurhidayat; Ameliyana Rizky Syamara Putri Akhmad Yani; Ghaniyya Dzihni Jayanti; Cahya Widya Wati; Nur Akhlis Sarihidaya Laksana (Infotekmesin, 2026)
Spent coffee grounds are organic waste that have the potential to be developed as raw material for biomass briquettes. This study aims to examine the effect of binder type, mixture ratio, and particle size on the characteristics of spent coffee grounds briquettes. Testing included calorific value using the Bomb Calorimeter method based on ASTM D 240-02, as well as moisture and ash content using the Gravimetric method. Results show that binder type was the most dominant factor. Briquettes with guar gum binder produced the highest average calorific value of 17,043.5 J/g (specimen 1) and the lowest ash content of 1.27 %wt, far superior to combustion residue briquettes, which yielded only 10,352.5 J/g with 28.78 %wt ash content. Fine particle size (<200 mesh) was shown to improve calorific value, while increasing the proportion of spent coffee grounds in residue-based briquettes effectively reduced ash content. All specimens exhibited moisture content below 15 %wt.